Burden of communicable diseases and cost of illness: Asia pacific region. (3rd July 2020) - Shah, Shahid; Abbas, Ghulam; Riaz, Nabeel; Anees ur Rehman,; Hanif, Muhammad; Rasool, Muhammad Fawad
ABSTRACT: Background: Communicable diseases such as AIDS/HIV, dengue fever, and malaria have a great burden and subsequent economic loss in the Asian region. The purpose of this article is to review the widespread burden of communicable diseases and related health-care burden for the patient in Asia and the Pacific. Areas covered: In Central Asia, the number of new AIDS cases increased by 29%. It is more endemic in the poor population with variations in the cost of illness. Dengue is prevalent in more than 100 countries, including the Asia-Pacific region. In Southeast Asia, the annual economic burden of dengue fever was between $ 610 and $ 1, 384 million, with a per capita cost of $ 1.06 to $ 2.41. Globally, 2.9 billion people are at risk of developing malaria, 90% of whom are residents of the Asia and Pacific region. The annual per capita cost of malaria control ranged from $ 0.11 to $ 39.06 and for elimination from $ 0.18 to $ 27. Expert opinion: The cost of AIDS, dengue, and malaria varies from country to country due to different health-care systems. The literature review has shown that the cost of dengue disease and malaria is poorly documented.